The Role of Organizational Practices in Enabling Sustainable Careers - Karstu, Joona (My University, 2025)
The transformation of work, digitalization, and economic uncertainty have brought the sustainability of careers to the forefront. The shift away from a traditional linear view of careers has moved toward paths shaped by the individual, context, and time. Especially in late-career settings, such as the social and health care sector, an aging workforce and rising retirement ages underscore the need to support employability, well-being, and productivity simultaneously. This thesis examines how organizational practices can strengthen sustainable careers. The topic is approached through a descriptive literature review that aims to form a comprehensive overview of organizational-level practices for enabling career sustainability. The theoretical lens is the sustainable careers framework. The review is structured into three areas: (1) training and development, (2) workload management, and (3) career path planning. In addition, age and career-stage differences, inclusiveness, and psychological safety are considered. Based on the findings, employer-provided, work-embedded learning and supervisor support increase performance and employability, and in late career credible development opportunities are associated with a higher expected retirement age. The balance of demands and resources is supported by autonomy, feedback, and clear goals. Chronically excessive demands, in turn, increase the risk of burnout. In career planning, transparent, life-course–scalable paths and career customization practices strengthen attachment when they are legitimized at the organizational level. Mentoring and clear learning paths benefit the early career stage in particular, while phased transitions, mentoring roles, and part-time options support late careers and the preservation of tacit knowledge. In conclusion, sustainable careers can be advanced through a practical triad: supervisor-supported competence development, the continuous alignment of job demands and resources, and transparent career paths that account for the life course. When implemented consistently and inclusively, these practices strengthen health, happiness, and productivity, and extend working lives.

Työelämän murros, digitalisaatio ja taloudellinen epävarmuus ovat nostaneet urien kestävyyden keskiöön. Perinteisestä lineaarisesta urakäsityksestä on siirrytty kohti polkuja, joita muovaavat yksilö, konteksti ja aika. Erityisesti myöhäisuralla, kuten sote-alalla, ikääntyvä työvoima ja nouseva eläkeikä korostavat tarvetta tukea samanaikaisesti työllistettävyyttä, hyvinvointia ja tuottavuutta. Tässä tutkielmassa tarkastellaan, miten organisaatiokäytännöillä voidaan vahvistaa kestäviä työuria. Aihetta lähestytään kuvailevan kirjallisuuskatsauksen avulla, jonka tavoitteena on muodostaa kattava kokonaiskuva organisaatiotason käytännöistä urakestävyyden mahdollistamiseksi. Teoreettisena kehyksenä hyödynnetään kestävien urien viitekehystä. Katsaus jäsentyy kolmeen osa-alueeseen: (1) osaamisen kehittäminen, (2) kuorman ja voimavarojen yhteensovittaminen sekä (3) urapolkujen suunnittelu. Lisäksi huomioidaan ikä- ja uravaihe-erot, inklusiivisuus sekä psykologinen turvallisuus. Tulosten perusteella työnantajan tarjoama, arjen työhön kytkeytyvä oppiminen ja esihenkilöiden tuki lisäävät suoriutumista ja työllistettävyyttä, ja myöhäisuralla uskottavat kehittymismahdollisuudet liittyvät korkeampaan odotettuun eläkeikään. Kuorman ja voimavarojen tasapainoa tukevat autonomia, palaute ja selkeät tavoitteet. Kroonisesti ylimitoitetut vaatimukset puolestaan kasvattavat uupumisriskiä. Urasuunnittelussa läpinäkyvät, elämänvaiheisiin skaalautuvat polut, sekä työurien räätälöinnin käytännöt vahvistavat kiinnittymistä, kun ne on legitimoitu organisaatiotasolla. Mentorointi ja selkeät oppimispolut hyödyttävät erityisesti uran alkuvaihetta, kun taas vaiheittaiset siirtymät, mentoriroolit ja osa-aikavaihtoehdot tukevat myöhäisuraa ja hiljaisen tiedon säilymistä. Johtopäätöksenä esitetään, että kestäviä uria voidaan edistää käytännöllisen triadin avulla: esihenkilötuettu osaamisen kehittäminen, kuorman ja resurssien jatkuva yhteensovittaminen, sekä läpinäkyvät, elämänkaaren huomioivat urapolut. Toteutettuna johdonmukaisesti ja inklusiivisesti nämä käytännöt vahvistavat terveyttä, onnellisuutta ja tuottavuutta, sekä pidentävät työuria.
Keywords: career development; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|